A quadratic B-spline Galerkin approach for solving a coupled KdV equation - Kutluay, Selcuk; Ucar, Yusuf (Mathematical Modelling and Analysis, 2013)
In this paper, a quadratic B-spline Galerkin finite element approach is applied to one-dimensional coupled KdV equation in order to obtain its numerical solutions. The performance of the method is examined on three test problems. Computed results are compared with the exact results and also other numerical results given in the literature. A Fourier stability analysis of the approach is also done.